Physiological action of UVB radiation on wheat seeds and sprouts (Triticum aestivum L.) - Sosnin, Eduard A.; Burenina, Anastasiya A.; Surnina, Elena N.; Fadeeva, Yulia Yu; Astafurova, Tatyana P. 1950- (Pulsed lasers and laser applications AMPL-2021 : the 15th International conference, September 12-17, 2021, Tomsk, Russia : abstracts)
This work continues the cycle of our research on the physiological effect of UVB radiation on plants. Two research cycles were conducted